Aberrant origin of the left coronary artery from the right coronary sinus with a common orifice with the right coronary artery - Jamal Ataya; Boushra Alkhattab; Nabeha Haytham Alibrahim; Somar Shalaby (Clinical Case Reports)
Key Clinical Message In patients with anomalous origin of the left main coronary artery, accurate classification is essential for effective management. Despite surgical refusal, successful stenting and medication can lead to favorable outcomes. Regular monitoring ensures ongoing cardiac health. Abstract Coronary artery anomalies, including anomalous origin of the left main coronary artery from the right sinus of Valsalva, are rare occurrences with varying clinical significance. Accurate classification of these anomalies is crucial for determining their implications and guiding management. A 50‐year‐old man presented with chest pain and was diagnosed with an anomalous origin of the left main coronary artery. Despite refusing surgery, successful stenting and medication led to a favorable outcome. Regular monitoring is scheduled. Accurate classification of coronary anomalies, such as the left main coronary artery anomaly described, is vital for effective management. Even when surgical intervention is declined, alternative treatments, such as stenting, can be successful. Regular monitoring ensures ongoing cardiac health.